PENGENDALIAN PERSEDIAAN OBAT GENERIK DENGAN METODE ANALISIS ABC, METODE ECONOMIC ORDER QUANTITY (EOQ), DAN REORDER POINT (ROP) DI APOTEK XYZ TAHUN 2017 - Stephanus Bimata Dyatmika (Modus, 2018)
This study aims to analyze the control of generic drug stock at XYZ Pharmacy in 2017. The data used are primary data and secondary data. Methods of data collection conducted in this research are observation, interview, and documentation. For the planning of generic drug procurement, in this research is done analysis of investment value to know which generic drug which belongs to group A, B, and C. Then do Economic Order Quantity (EOQ) calculation to know economic order quantity and Reorder Point (ROP) to know the point of re-ordering the generic drugs of the 2017 period. The result of analysis shows the analysis of ABC investment there are drugs that enter into group A as many as 11 kinds of drugs or 16,42% from all generic drug, absorb 70,41% investment, group B as many as 15 drug type or 22,39% from all generic drug, absorbing 20.09% investment. While group C counted 41 types of drugs or 61.19% of all generic drugs the drug items absorbed only 9.49% investment. EOQ and ROP calculations are also obtained for the period of 2017. The existence of these calculations is useful to help pharmacies in the procurement of generic drugs so that there is a balance between service levels and costs.Keywords: inventory, generic drugs, ABC analysis, Economic Order Quantity,  Reorder Point